Designing a library tourism model based on local cultural storytelling - Rejeki, Diah Sri; Agustine, Merryam; Saputera, Denny; Surya, Ibrahim Adi; Rukmana, Evi Nursanti; Taharuddin, Nurul Shima (Universitas Padjadjaran, 2025)
Background: Few reading communities have developed systematic literacy tourism models centering local narratives. Purpose: This study designs and validates a culturally embedded literacy tourism model at Pabukon Ngadongeng Reading Community, Sumedang. Methods: Using design thinking methodology (empathize, definition, ideation, prototyping, testing), data were collected through ethnographic observations, interviews, and focus group discussions. The prototype featured a 90-minute narrative route incorporating Sundanese storytelling (Nini Anteh), traditional games (paciwitciwit lutung, oray-orayan), and reflective discussions. Results: Results demonstrate measurable multi-dimensional impacts. Educationally, children exhibited significantly enhanced narrative comprehension when stories were delivered orally versus textually, with sustained active participation throughout sessions. The integration of folklore with traditional games created embodied learning experiences that improved reading retention and contextual understanding. Socially, the model fostered intergenerational dialogue among local storytellers, volunteers, children, and parents, strengthening community cohesion. Post-implementation, multiple schools independently contacted the reading community requesting program replication, indicating strong social demand and perceived value. Culturally, participants demonstrated deepened emotional connections to Sundanese heritage, with Nini Anteh eliciting particularly strong responses regarding loyalty and familial bonds. Children expressed heightened pride in regional identity and increased engagement with local cultural narratives. Digital documentation through Instagram and integration with the Sumedang Reading Community Forum website extended program reach beyond physical sessions, creating accessible archives for broader literacy networks. Conclusion: The study concludes that participatory, culturally oriented literacy programs transform local knowledge into transferable educational frameworks. Limitations include single-location implementation and analog process constraints. Implications: Theoretically, this demonstrates that modularity frameworks can resolve authenticity-scalability tensions in cultural tourism. Practically, the model provides a replicable blueprint for reading communities, with policy implications for Perpustakaan Nasional Republik Indonesia literacy strategies and UNESCO Memory of the World heritage preservation. Future research should explore multi-site validation and hybrid analog-digital models.